Managing Agricultural Production Risk : Innovations in Developing Countries - World Bank (Washington, DC, 2012)
This document presents innovations in agricultural risk management for natural disaster risk, with the focus on defining practical roles for governments of developing countries and the World Bank in developing risk management strategies. The paper includes the following content: introduction; risk and risk management in agriculture, including informal and formal mechanisms; approaches to agricultural risk in developed countries; innovation in managing production risk - index insurance; new approaches to agricultural risk management in developing countries; from theory to practice: pilot projects for agricultural risk transfer in developing countries; and potential roles for governments and the World Bank.